The essence of legal components of economic risks - S. V. Yevdokimenko (Bulletin of Kharkiv National University of Internal Affairs)
This research is one of the first attempts in the Ukrainian legal science in determining the essence and features of legal components of economic risks taking into account the latest achievements of science. It has been emphasized that theoretical basis for determining the concept of “risk” is widely researched in the scientific literature, but the problem of legal components of the economic risks has been insufficiently highlighted.